Determining the effect size of aerobic exercise training on the standard lipid profile in sedentary adults with three or more metabolic syndrome factors: a systematic review and meta-analysis of randomised controlled trials. Issue 18 (30th June 2021) - Wood, Gina; Taylor, Emily; Ng, Vanessa; Murrell, Anna; Patil, Aditya; van der Touw, Tom; Sigal, Ronald; Wolden, Mitch; Smart, Neil
Abstract : Objectives: To estimate the change in the standard lipid profile (SLP) of adults diagnosed with ≥3 metabolic syndrome (MetS) factors following aerobic exercise training (AET); and to investigate whether study/intervention covariates are associated with this change. Design: Systematic review with univariate meta-analysis and meta-regression. Data sources: English language searches of online databases from inception until July 2020. Eligibility criteria: (1) Published randomised controlled human trials with study population ≥10 per group; (2) sedentary adults with ≥3 MetS factors but otherwise free of chronic disease, not pregnant/lactating; (3) AET-only intervention with duration ≥12 weeks; and (4) reporting pre–post intervention SLP outcomes. Results: Various univariate meta-analyses pooled 48 data sets of 2990 participants. Aerobic exercise training significantly ( P <.001) improved all lipids (mmol/L mean difference ranges, 95% CIs): total cholesterol, –0.19 (–0.26 to –0.12) to –0.29 (−0.36 to –0.21); triglycerides, −0.17 (–0.19 to –0.14) to –0.18 (−0.24 to –0.13); high-density lipoprotein-cholesterol (HDL-C), 0.05 (0.03 to 0.07) to 0.10 (0.05 to 0.15); and low-density lipoprotein-cholesterol (LDL-C), –0.12 (–0.16 to –0.9) to –0.20 (−0.25 to –0.14). Meta-regression showed that intensity may explain change in triglycerides and volume may explain change in HDL-C and LDL-C. Conclusion: Aerobic exercise training positively changes the SLP of sedentary and otherwise healthy adults with ≥3 MetS factors. Adjusting AET intervention training variables may increase the effects of AET on triglycerides and HDL-C. PROSPERO registration number: CRD42020151925.